Numerical study of few-cycle pulses generation from supercontinuum in ANDi-PCF - Shulika, O.; Sukhoivanov, I.; Iakushev, S.; Guryev, I.; Andrade Lucio, J.; Ibarra Manzano, O.; Barrientos García, A.; Ramos Ortiz, G. (Acta Universitaria, 2013)
This paper presents the design of all-normal dispersion photonic-crystal fiber optimized for pulse-preserving supercontinuum generation near 800 nm. The supercontinuum generation is analyzed numerically addressing the role of pump pulse energy and the pump wavelength deviation from the zeroth point of third-order dispersion. We have also shown that supercontinuum generated in designed ANDi-PCF from a few nanojoule 100 fs pulses can be efficiently compressed down to a sub-10-fs pulse with a simple quadratic compressor.
Keywords: Array; Array; Array; Array